Immune response in children with COVID‐19 is characterized by lower levels of T‐cell activation than infected adults. Issue 9 (29th July 2020) - Moratto, Daniele; Giacomelli, Mauro; Chiarini, Marco; Savarè, Lucia; Saccani, Barbara; Motta, Mario; Timpano, Silviana; Poli, Piercarlo; Paghera, Simone; Imberti, Luisa; Cannizzo, Stefania; Quiros‐Roldan, Eugenia; et al.
Abstract : Study of immunological features of immune response in 14 children (aged from 12 days up to 15 years) and of 10 adults who developed COVID‐19 show increased number of activated CD4 and CD8 cells expressing DR and higher plasmatic levels of IL‐12 and IL‐1β in adults with COVID‐19, but not in children. In addition, plasmatic levels of CCL5/RANTES are higher in children and adults with COVID‐19, while CXCL9/MIG was only increased in adults. Higher number of activated T cells and expression of IL‐12 and CXCL9 suggest prominent Th1 polarization of immune response against SARS‐CoV2 in infected adults as compared with children.